F♯ for quantitative finance : an introductory guide to utilizing F♯ for quantitative finance leveraging the .NET platform - Astborg, Johan (Community experience distilled., 2013)
To develop your confidence in F♯, this tutorial will first introduce you to simpler tasks such as curve fitting. You will then advance to more complex tasks such as implementing algorithms for trading semi-automation in a practical scenario-based format. If you are a data analyst or a practitioner in quantitative finance, economics, or mathematics and wish to learn how to use F♯ as a functional programming language, this book is for you. You should have a basic conceptual understanding of financial concepts and models. Elementary knowledge of the .NET framework would also be helpful.